Collision tumors in the thyroid: papillary carcinoma and metastases of clear cell renal cell carcinoma - Aranda Villalobos, Dora L. (2021)
Collision tumors are rare neoplasms, they require combination therapy for the treatment of each tumor independently. We describe the case of a 55 year old patient diagnosed with clear cell renal cell carcinoma; whole body computed tomography reported pulmonary and hepatic nodules suggestive of metastatic disease. Oncology indicated sunitib therapy. Eleven months later, evaluation with computed tomography reported multiple thyroid nodules. Total thyroidectomy was performed, with anatomo-pathological report: papillary thyroid carcinoma and metastases of clear cell renal cell carcinoma. He received ablation with 80 mCi of radioactive iodine (I-131); then thyroid hormone suppressive therapy with levothyroxine.